TINJAUAN YURIDIS TERHADAP PERMOHONAN SITA MARITAL ATAS SENGKETA HARTA BERSAMA DILUAR GUGATAN PERCERAIAN MENURUT UNDANG-UNDANG NO. 1 TAHUN 1974 TENTANG PERKAWINAN DAN KOMPILASI HUKUM ISLAM (STUDI KASUS PUTUSAN NO. 2188/PDT.G/2012/PA JS) - Azirah Azirah; Hasim Purba; Idha Aprilyana; Sutiarnoto Sutiarnoto (Universitas Sumatera Utara, 2017)
ABSTRACT Joint property is one of the factors that cause a friction and a conflict in a marriage. The conflict appears because one of the parties usesthe joint property extravagantly. Consequently, the injured party can file for “marital confiscation”. The research results show thatthe requestsof marital confiscation on the conflict of the joint property are divided into two that is;firstly, marital confiscation done because of divorce claim as stipulated in Article 24 paragraph (2) letter c of PP No. 9/1975, Article 78 letter c UU No.7/1989, Article 136 paragraph (2) letter b of KHI, and secondly out of divorce claim in Article 95 paragraph (1) of KHI and Article 186 of Civil Code. However, in the broader sense, the request covers some conflicts between a husband and a wife that is in a divorce case, distribution of joint property case, and actions that endanger the joint property. In the ruling of civil case No. 2188/Pdt.G/2012/PA JS, it is found out that the reason why the marital confiscation is filed by a wife as the Petitioner is that there is an allegation or a suspicion that her husband as the Respondenthas a backstreet relationship with another woman that in this case the Respondenthas been reasonably suspected to use the joint property extravagantly. In the Ruling, the Judge of South Jakarta Religious Court has refused all of the Petitioner’s requests for the marital confiscation because the evidence element is not fulfilled during the hearing process of the joint property case. Besides, the Penal of Judges considers that the application of the article used by the Petitioner is not appropriate. Therefore, people should be more careful to apply the article on the marital confiscation they fileso that the legal effort done is not useless. Keywords: Marital Confiscation, Joint Property, Marriage